STRATEGI GURU DALAM MENGEMBANGKAN KEMANDIRIAN DAN INTERAKSI SOSIAL ANAK KEMBAR IDENTIK DI PAUD KB FATIMAH AZ ZAHRA - Sarmita; Suryani; Windi Permana; Elih Minarti; Nafira Fitri Maharani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Early Childhood Education (ECE) is a very important initial stage in a child’s development, particularly in shaping independence and social interaction skills. At this stage, children begin to learn about themselves, their environment, and how to build social relationships with others. Identical twins have unique characteristics, including a very high level of emotional closeness and a tendency to always be together in various activities. This condition often causes identical twins to experience challenges in developing independence and social interaction skills, especially in adapting to a broader social environment outside their twin relationship. This study aims to analyze teachers’ strategies in developing the independence and social interaction of identical twins in PAUD KB Fatimah Az Zahra. This research uses a descriptive qualitative approach. Data collection techniques include observation, interviews, and documentation. The research subjects consist of classroom teachers, identical twin children, and parents as supporting data sources. The results of the study show that teachers’ strategies in developing the independence and social interaction of identical twins are carried out through several approaches, namely habituation of independent activities in daily routines, the implementation of group-based learning to enhance peer interaction, individualized approaches according to each child’s needs, and intensive collaboration between teachers and parents in supporting the children’s development both at school and at home. These strategies have proven effective in improving children’s independence and expanding their social interaction skills within their environment.